Co-encapsulation of siRNA with non-coding pDNA or Poly-L-glutamic acid in DODAB:MO (2:1) liposomes for enhanced gene silencing - Almeida, Fernando Henriques (2015)
Dissertação de mestrado em Biofísica e Bionanossistemas